Prevalence, perceptions and factors associated with non-adherence to hepatotoxicity monitoring among people living with HIV on tuberculosis preventive treatment at Mulago ISS clinic - Kevin Naturinda; Irene Andia Biraro; Ezekiel Mupere; Anthony Muyunga; Racheal Namutale Nalule; Benard Owori; Linda Dorothy Akot; Jovan Mugerwa; Arthur Shem Kasambula; Joseph Rubeihayo; Joan Kalyango (PLoS ONE, 2026)
Introduction Hepatotoxicity monitoring is recommended for people living with HIV (PLHIV) enrolled on tuberculosis preventive treatment (TPT). Despite a 7.3% hepatotoxicity incidence reported in a multi-country study, implementation and adherence to hepatotoxicity monitoring remains low. We aimed at determining the prevalence, patients’ and health workers’ perceptions, and factors associated with non-adherence to hepatotoxicity monitoring among adult PLHIV receiving TPT at Mulago ISS clinic. Methods A sequential explanatory mixed methods study was carried among health workers and adult PLHIV enrolled on TPT between 2022 and 2023 at Mulago ISS clinic. The quantitative and qualitative components utilized a cross-sectional and an exploratory descriptive design respectively. A data abstraction tool was used to obtain quantitative data from files and electronic medical records of a systematic random sample of 390 patients. The qualitative study utilized interview guides to conduct in-depth audio recorded interviews for five patients and five health workers. Descriptive statistics and modified Poisson regression analyses were performed for the quantitative data. Deductive thematic analysis based on the health belief model was utilized for the qualitative data. Results The prevalence of non-adherence to hepatotoxicity monitoring was 87.4% (95%CI: 83.7–90.4). The prevalence of non-adherence to hepatotoxicity monitoring was 85% lower in PLHIV that received primary TPT as compared to those on secondary TPT (aPR-0.15, 95% CI: 0.04–0.55). The qualitative findings revealed varied perceptions about non-adherence to hepatotoxicity monitoring that included awareness of associated risks, perceived benefits of monitoring, and confidence in taking action, while also identifying perceived barriers such as financial, knowledge and communication challenges. Conclusions The prevalence of non-adherence to hepatotoxicity monitoring was high within this pharmacovigilance sentinel site, given its clinical importance in HIV care and clear recommendations in the national HIV treatment guidelines. Health authorities should implement policies promoting hepatotoxicity monitoring in pharmacovigilance sentinel sites, especially for patients receiving secondary TPT, and allocate resources to support this initiative.